Philosophy of the state: main models of civilisational development - Vorobyova, Svetlana V.; Liahchylin, Anatoly A. (Journal of the Belarusian State University. Sociology, 2026)
The article reveals the philosophical foundations of the origin of the state in the context of civilisational development. To this end, firstly, the concepts of the origin of the state are systematised, the factors marked as decisive circumstances of its formation are identified. Secondly, on the one hand, the dependence of the origin of the state on civilisational development is substantiated, on the other hand, the immutability of its goal: organisation and management of society for its survival and development. Thirdly, it is shown that each concept forms its own image of the state as a self-organising society. As a result, in the analytical argumentation it is necessary to avoid negative assessments of these concepts, indicating which factors of state formation are not taken into account in them, and to focus on positive assessments, taking into account the signs and characteristics of statehood identified in them. Fourthly, the boundaries of the construction of explanatory models of the origin and development of the state are outlined, which are conditioned by the search for answers to the challenges of the time. Models of democratic, legal and social states, differing in their foundations, ideas, goals and characteristics, have become generally significant. Fifthly, a draft civilisational model of Belarusian statehood is presented in the context of internal (democratic, legal and social aspects of statehood) and external geopolitical factors in the context of the transition to a multi-polar world.
Keywords: philosophy of the state; concepts of the origin of the state; civilisational development of society; democratic state; rule of law; social state; model of Belarusian statehood